Believing in God the Father: Interpreting a phrase from the Apostle"s Creed - Sarot, Marcel (HTS teologiese studies, 2016)
In our days, the creedal phrase ‘I believe in God the Father almighty’ is interpreted primarilyalong Trinitarian lines: It is applied to God as the Father of Jesus Christ. Here I argue that ithas a dual background: in Jesus’ prayer practice, in which He consistently addressed God as‘Father’, and in the Hellenistic habit of referring to the Creator as ‘Father’. I discuss Jesus’ useof the term ‘Father’ against its Old Testament background, and argue that it primarily pointsto the intimacy of Jesus’ relationship with His father. Against the Hellenistic background,however, the metaphor ‘Father’ means ‘he who brings forth effortlessly’. Finally, I discusssome gender issues connected with the use of the term ‘Father’ for God.